FIB-4 and APRI scores for predicting severe fibrosis in chronic hepatitis C - a developing country's perspective in DAA era - Uros Karic; Ivana Pesic-Pavlovic; Goran Stevanovic; Milos Korac; Natasa Nikolic; Aleksandra Radovanovic-Spurnic; Aleksandra Barac; Nikola Mitrovic; Aleksandar Markovic; Marko Markovic; Anita Petkovic; Ivana Ostojic; et al. (Journal of Infection in Developing Countries)
Introduction: Chronic Hepatitis C Virus (HCV) infection leads to progressive fibrosis making fibrosis staging necessary in the evaluation of such patients. Different fibrosis scores are emerging as possible non-invasive alternatives for liver biopsy. The Fibrosis-4 Index (FIB-4) and AST to Platelet Ratio Index (APRI) scores are the most widely used and the most extensively tested. This study aims to determine if it was possible to accurately use these to identify patients that are unlikely to have severe fibrosis.